RESILIENSI LEMBAGA PENDIDIKAN ISLAM: STRATEGI MENJAGA IDENTITAS BUDAYA LOKAL DI TENGAH ARUS GLOBALISASI - Ali Fakhri Amrullah Suwanda; Ahmad Khori; Pupu Maspupah (STKIP Subang, 2026)
Globalization and digital transformation have significantly reshaped educational systems, including Islamic educational institutions in Indonesia. The increasingly rapid flow of cultural exchange has not only created opportunities for modernization but also generated challenges in the form of weakening local cultural identities due to the dominance of global values. In this context, Islamic educational institutions are required to preserve Islamic values and local wisdom while remaining relevant to contemporary developments. This study aims to analyze the resilience of Islamic educational institutions in maintaining local cultural identity amid the pressures of globalization. The research employs a qualitative approach using a library research method through the analysis of various literature related to globalization, Islamic education, digital transformation, and educational leadership. The findings reveal that the resilience of Islamic educational institutions should not merely be understood as the ability to survive, but rather as an adaptive and transformative capacity to selectively manage change. The main strategies identified include: (1) reconstructing curricula based on local wisdom as contextualized living values; (2) implementing ethically grounded digital transformation by positioning technology as a means (wasilah) for character building; and (3) strengthening transformational leadership with a glocal vision that integrates global perspectives with local values. Therefore, the resilience of Islamic educational institutions lies in their ability to critically negotiate cultural changes while preserving Islamic and Indonesian identities within the dynamics of globalization.